Дело, которому ты служишь - Герман Юрий Павлович (Русская литература. Большие книги, 2023)
Экземпляры: ф. 9 (20240513) / Инвентарный номер: 67922 / Цена: 974.00 / Авт.знак: Г 38 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6